Molecular identification and sequencing of Pseudomonas aeruginosa 16S rRNA gene isolated from a variety of raw cow milk samplesin Iraq - Saeed, AA; Mayea, KQ; Shalal, SH (Journal of the Hellenic Veterinary Medical Society, 2023)
Pseudomonas aeruginosa is Gram-negative bacterium which is notably known as a pathogen in humans, animals, and plants.Suspect raw milk samples were analyzed to amplify the 16S rRNA gene and confirm Pseudomonas aeruginosa strains. This study was conducted at different farmland in diwaniya and al-Najaf., a total of 70 samples were collected (28 from mastitic cows and 42 from apparently healthy cows ) the detection of the 16S rRNA gene in this study revealed 11 ( positive isolates of Pseudomonas were identified from samples after culture on cetrimid agar. New sets of primer pairs were designed using the NCBI database search tool. The phylogenetic relationship between different strains of Pseudomonas aeruginosa has been studied through using 16S rRNA gene region sequencing. A distance tree was constructed to determine the genetic similarity between species. as result of the 9 isolate gene sequencing, it was determined, and submitted in GenBank accession numbers (MZ799357, MZ817077, MZ820788, MZ820878 , MZ821016, MZ823355, MZ823356 MZ823387. MZ823389) , in conclusion the PCR is a reliable technique that identifies Pseudomonas aeruginosa at the molecular level